Climate–ecological–economic modelling for the cost-effective spatiotemporal allocation of conservation measures in cultural landscapes facing climate change. Issue 1 (16th February 2022) - Gerling, Charlotte; Drechsler, Martin; Keuler, Klaus; Leins, Johannes A; Radtke, Kai; Schulz, Björn; Sturm, Astrid; Wätzold, Frank
Abstract: Climate change has become a key threat to biodiversity. As a response to climate change, species may adapt spatially (with range shifts) and temporally (with phenological adaptations), which may alter the impact of conservation measures. In cultural landscapes, where conservation often depends on specifically timed land use, climate change may also induce spatial changes in opportunity costs of conservation measures and with respect to their timing. Thus, previously cost-effectiveness conservation efforts may become less cost-effective. We develop a climate–ecological–economic model to investigate climate change-induced modifications of the cost-effective spatiotemporal allocation of conservation measures. We apply the model to a case study to investigate the cost-effectiveness of grassland measures to conserve the large marsh grasshopper in northern Germany for the periods 2020–39 and 2060–79. Our model shows modifications in the cost-effective spatial allocation of conservation measures and that the timing of measures adapted to phenological changes remains cost-effective under climate change.